Stress Management Strategy for Kindergarten Teachers Based on Islamic Values - Jazilatul Auniyah; Sofyan Tsauri; Zainal Abidin (Al-Qalam Institue, 2026)
Teacher stress management has become an important issue in educational institutions, especially in early childhood education where teachers face high emotional and pedagogical demands. This study aims to analyze the formulation, implementation, and evaluation of strategic stress management for teachers at kindergarten. The study employed a qualitative approach with a phenomenological design. Data were collected through observation, in-depth interviews, and documentation involving school principals and teachers as key informants. The findings reveal that strategic stress management in the institution is carried out through three stages: strategy formulation based on institutional vision, identification of stressors, and strengthening Islamic values; strategy implementation through problem-focused coping and emotion-focused coping approaches; and strategy evaluation through monitoring teachers’ emotional stability, work commitment, and teaching effectiveness. The study also found that Islamic values such as patience, sincerity, deliberation, and tawakkal function as important foundations in strengthening teachers’ psychological resilience. The research contributes conceptually to the development of Islamic educational management, particularly in integrating strategic management and stress management within educational institutions. Practically, this study offers an institutional stress management model that is preventive, systematic, and spiritually oriented in supporting teacher well-being and improving educational quality.